2010
DOI: 10.1614/wt-d-09-00004.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Rolled-rye Cover Crop for Weed Suppression in No-Till Soybeans

Abstract: Cover crop management with a roller/crimper might reduce the need for herbicide. Weed suppression from a rolled cereal rye cover crop was compared to no cover crop with and without postemergence herbicide application in no-till soybean. The experiment was designed as a two-way factorial with rye termination and soybean planting date as the first factor and weed control treatment as the second. Cereal rye was drill-seeded in late September and managed using glyphosate followed by a roller/crimper in the spring.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 13 publications
8
77
0
Order By: Relevance
“…For example, rye biomass increased by 37 to 100% when terminated 10 to 14 d after the normal early rye termination date, with subsequent increases in weed suppression (Mischler et al, 2010;Mirsky et al, 2011;Nord et al, 2012). Indeed, delaying termination would allow for more biomass accumulation, which is essential for weed smothering by the cover crop residues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rye biomass increased by 37 to 100% when terminated 10 to 14 d after the normal early rye termination date, with subsequent increases in weed suppression (Mischler et al, 2010;Mirsky et al, 2011;Nord et al, 2012). Indeed, delaying termination would allow for more biomass accumulation, which is essential for weed smothering by the cover crop residues.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions for weed emergence were more favorable due to reduced mulch soil coverage and less cover crop biomass in 2015 (Table 2). Mischler et al [41] observed high weed control efficacy, similar to a post-emergence herbicide application, when using rye as cover crop mulch at Rock Springs and Landisville, PA, USA in 2007. Liebl et al [9] presented similar results for a four-year study on soybeans and cover crops in Urbana, IL, USA.…”
Section: Weed Densitymentioning
confidence: 99%
“…In southern Wisconsin, weed biomass in early July was reduced by 62% in rye mulch compared with stale seedbeds 12 . In central Pennsylvania, mid-summer weed biomass reduction in soybean due to rolled and crimped winter rye compared with bare soil across five site-years was 15, 53, 91, 92 and 93% 18 . Lastly, in the absence of herbicides, rolled and crimped rye in Alabama provided 58, 69 and 83% weed control over 3 years 16 .…”
Section: Weed Emergence Biomass and Hand-weedingmentioning
confidence: 97%